The Problematic Experience of Players' Mutations Between Clubs: Discovering the Social Adaptability Skills Required - Owiti, Samuel; Hauw, Denis (Frontiers in Sports and Active Living, 2021)
Objective: In the sports environment, the unpredictable nature of events and occurrences requires athletes to adapt to new challenges embedded in their milieu. As a result of the uncertainty and the dynamic nature of the sporting environment, these adaptations might lead to inconsistencies, critical situations and finally drop out. Considering the importance of successful transitions and the complexity of these adaptations, we aimed to identify the social adaptability skills and attributes and how they are applied during club to club transitions. Design and method: Twenty professional basketball players (age range 20 - 36; Mean = 26.05, SD = 4.12), who had played under different coaches (coach range 4 – 15; Mean = 8.65, SD = 2.92), and also played for (club range 1 – 10; Mean = 5.20, SD = 2.57) took part in semi-structured interviews regarding their experiences during club to club mutations. A Grounded Theory approach was employed throughout the data collection and analysis, and interview transcripts were analysed using open and axial coding. We established methodological rigor by incorporating various verification strategies during the research process. Results and conclusions: We identified four general dimensions detailing athletes’ mutation experiences (coach, teammates, club, and family/friends) whenever they changed clubs. Additionally, results indicated that many adaptability skills required during transitions between clubs included: self-discipline, motivation, autonomy, interpersonal skills, positive thinking, and goal-setting. The emergent theory provides coaches, athletes, sport psychologists, and national sport organizations with an understanding of the challenge’s athletes encounter during club to club change.